Enhanced bacterial inhibition and photocatalyzed degradation of industrial contaminants by polyethylene glycol capped PbWO4 nanoparticles. (19th May 2023) - Asha, S.; Bakri, Marwah; El Manna, Chadlia; Sasi Florence, S.; Sarojini, V.; Hentry, C.; Bindhu, M. R.
Abstract: Lead tungstate nanoparticles (PbWO4 NPs) and PEG capped PbWO4 nanoparticles (PEG/PbWO4 NPs) were synthesized by co-precipitation technique. Vibrational, structural, optical and morphological properties of the as-prepared nanoparticles were observed by FTIR, XRD, UV-vis and SEM techniques. These nanoparticles show a tetragonal stolzite crystalline structure. The quantum confinement of nanoparticles was confirmed by UV-vis spectrum. Since polymeric modifying agent, polyethylene glycol (PEG) performs as a stabilizer and also helped to unite the surface of the PbWO4 NPs. FTIR established the functional groups in PEG united with the PbWO4 NPs and reduction took place in the reaction medium. The adsorbed PEG onto the PbWO4 NPs initiated the negative charge onto the particle surface and thus repelled the particles away from one another, hindering them from aggregation. The formation of quasi-octahedrons was confirmed from SEM images. The consequences of the antimicrobial study prove that the better capability of PEG/PbWO4 NPs to inhibit the growth of Staphylococcus aureus, Pseudomonas aeruginosa, and Aspergillus niger . This study signified that PEG is an effective surfactant for morphology control, reduction of crystallite size, photocatalytic degradation of methyl orange and antimicrobial activity of PbWO4, maybe because of the steric impediment it grants.